2018
DOI: 10.1213/ane.0000000000003337
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Resuscitation Skills in Health Care Providers at a Zambian Tertiary Center, and Comparison to World Health Organization Standards

Abstract: Newborn resuscitation skills among health care professionals are varied. Midwives lead the majority of deliveries with anesthesiologists and pediatricians only being present at operative or high-risk births. It is therefore common that midwifery practitioners will initiate resuscitation. Despite this, midwives perform poorly when compared to anesthesia and pediatric residents. To address this discrepancy, a multidisciplinary, simulation-based newborn resuscitation program should be considered with continual cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
2
4
0
1
Order By: Relevance
“…[7,10,17] Midwives and Nurses provided NR to the majority of neonates (94.2%) than other HCP (5.8%), similar to a study conducted in Zambia on NR skills in HCP. [2,18] Our findings also showed that HCPs with more than one-year maternity unit experience (76.9%) did more resuscitation than those with less than one year experience (21.3%). These findings were similar to other studies identified by WHO indicated that a more extended period of working on the same unit enhances the HCPs' clinical practice, self-efficacy, and competency in NR skills.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…[7,10,17] Midwives and Nurses provided NR to the majority of neonates (94.2%) than other HCP (5.8%), similar to a study conducted in Zambia on NR skills in HCP. [2,18] Our findings also showed that HCPs with more than one-year maternity unit experience (76.9%) did more resuscitation than those with less than one year experience (21.3%). These findings were similar to other studies identified by WHO indicated that a more extended period of working on the same unit enhances the HCPs' clinical practice, self-efficacy, and competency in NR skills.…”
Section: Discussionsupporting
confidence: 58%
“…The absence of clocks was similar to a study conducted in Zambia. [2] But in contrast to a survey in Vietnam, whereby 50.3% of the 187 health facilities had clocks. [24] Protocols and guidelines were present for NR, with over half (55.2%) having visual NR action plans and guidelines, and NR flip charts (55.2%) available on the labor and maternity theater units.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Literatürde Mistry ve ark. 'nın (40) yaptıkları çalışmada düşük gerçeklikli simülasyonla verilen yenidoğan resüsitasyon eğitimi sonrası katılımcıların çoğunun yetersiz performans gösterdikleri, başka bir çalışmada ise düşük gerçeklikli simülasyon kullanılarak verilen yenidoğan resüsitasyon eğitiminin katılımcıların bilgi ve beceri düzeylerini geliştirdiği saptanmıştır (41) . Yüksek gerçeklikli simülasyon kullanılan iki çalışmada öğrencilerin, bilgi, güven ve becerilerinin geliştiği (19,42) , ancak başka bir çalışmada ise katılımcıların teknik ve teknik olmayan becerileri üzerinde sınırlı bir etkiye sahip olduğu saptanmıştır (43) .…”
Section: Bulgularunclassified